The effectiveness and acceptability of systemic enzyme therapy in the complex treatment of vulvovaginitis caused by opportunistic microorganisms: Open-label single-center prospective comparative randomized study - Vera N. Prilepskaya; Elena A. Mezhevitinova; Patimat R. Abakarova; Andrey E. Donnikov; Ada T. Uruymagova (Гинекология, 2024)
Background. Vulvovaginal infections are the most common, studied, and still causing many questions. It has been established that the disturbance of the ratio of the vaginal microbiota components does not always lead to a disorder since the development and outcome of the disorder largely depend on the state of the macroorganism, including the state of its immune system. To date, the only method for assessing the state of local immunity is smear microscopy with counting leukocytes. An alternative to leukocyte counting is the assessment of immunological parameters (e.g., the transcriptional profile of cytokine genes). An integrated approach to assessing the state of microbiocenosis (the ratio of lactobacilli and opportunistic pathogens) and local mucosal immunity, considering the individual genetic characteristics of patients and microorganisms, makes it possible to optimize treatment methods for vaginitis. One of the ways to increase the effectiveness of treatment and prevention of the recurrence of infectious and inflammatory diseases in gynecology is systemic enzyme therapy based on the complex effect of a specially selected combination of plant and animal origin enzymes on key physiological and pathophysiological processes in the body.